Transient brachial monoparesis following epidural anesthesia for cesarean section - Tejesh C Anandaswamy; Manjunath A Chikkapillappa; Geetha C Rajappa; Shivakumar Shivanna (Wolters Kluwer Medknow Publications, 2011)
Monoparesis following lumbar epidural block is a rare occurrence, with few cases reported in the literature. We report development of transient brachial monoparesis following epidural anesthesia in a parturient for cesarean section. The patient received a mixture of 15 mL of 2% lignocaine with 50 mcg fentanyl epidurally to achieve a blockade up to T6 level. She remained hemodynamically stable throughout the procedure, with no respiratory distress or desaturation. However, near the end of surgery, she developed weakness in the right upper limb. The weakness lasted for 90 min, followed by complete neurological recovery. Subsequent hospital stay was uneventful.